An Analysis of the Implementation of Senam Anak Indonesia Hebat on the Gross Motor Skills of Children Aged 5–6 Years - Mintarsih, Mintarsih; Dewi, Nurul Fitria Kumala; Nurjaman, Iman (Universitas Muhammadiyah Mataram, 2026)
This study is motivated by the suboptimal development of gross motor skills among children aged 5–6 years, as well as the limited research on the implementation of Senam Anak Indonesia Hebat (SAIH) as a structured habituation program in early childhood education. This study aims to analyze the implementation of Senam Anak Indonesia Hebat (SAIH) in developing gross motor skills of children aged 5–6 years at KB Bestari, as well as to identify its supporting factors and challenges. This research employed a descriptive qualitative approach involving 14 children (6 boys and 8 girls) and one Group B teacher as subjects. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The results indicate that the structured implementation of SAIH twice a week contributes positively to children’s balance, strength, and movement coordination. A total of 85.7% of children were categorized as Developing as Expected (BSH) and Beginning to Develop (MB). Supporting factors include teacher readiness, appropriate music selection, and gradual movement design, while challenges mainly involve maintaining children’s focus and mastering cross-lateral coordination. Therefore, SAIH can be considered an effective physical activity–based instructional strategy to optimize early childhood gross motor development.